A Study on Association Between Passive Smoking and Childhood Tuberculosis in Surat City: A Case Control Study - Parmar, Gaurang; Parmar, Sahil; Amin, Sunilkumar; Patel, Natvarlal B (National Journal of Medical Research, 2025)
Background: Factors contributing to the high burden of childhood TB in the country are not yet fully understood. Hence the present study was undertaken to determine the risk factors, including passive smoking, for TB in children between 0-14 years of age in Surat city. Methodology: The present study was a case-control study conducted on eligible cases and controls in a ratio of tuberculous cases to non-tuberculous controls of 1:2. Case is defined as incident cases of TB in children between the age group of 0-14 years residing in Surat city. The data was collected using pre-designed structured questionnaire developed with the help of all the stake holders. This questionnaire was filled up by oral interview technique. Results: The study found 39 children with family history of smoker, of which passive smoking was found in 53.8% cases and 73.0% controls. The study could not find statistically significant association between passive smoking and childhood tuberculosis. No immunization with BCG was found in 26.2% cases compared to 10.8% controls [OR=2.93 (1.25-6.90), p <0.05]. Conclusion: Age of more than 10 years, nuclear family, absence of BCG vaccination and past history of tuberculosis are significantly associated with cases of childhood tuberculosis compare to non-tuberculous children. The present study could not found association between passive smoking and childhood tuberculosis.